Teaching Speaking in Senior High School by Pair Work Technique - Ika Purnama Sari; Yanti Anggraini; S Setiawati; Anita Purba; Noor Faridha (CV. Media Digital Publikasi Indonesia, 2024)
This research was conducted to increase students' speaking skills by using the Pair Work Technique. The researcher wanted to find out whether the Pair Work Technique can increase students' speaking skills; besides that, the researcher wanted to know the students' perception as long as thought by the Pair Work Technique. This researcher used Action Class Research. The subject was Class X IPS MAN Pematangsiantar. This research uses quantitative and qualitative methods. In quantitative the researcher use Pre Test and Post Test. In the test, the average of students was 66,77, and in the post-test Test, the students could increase their average score to 80,65. Besides that, the researcher also makes an observation about students' perception as long as taught by Pair Work Technique. There are 31% of students feel studying happily, 29% of students feel brave and active in giving their opinions, 26% of students feel motivated, and 14% of students are becoming helpful in studying when teaching and learning process using Pair Work techniques. It can concluded that Pair work was successful in improving students’ speaking skills